Pengaruh Aksesibilitas dan Kesehatan Masyarakat terhadap Ketahanan Pangan di Papua dan Papua Barat Tahun 2022 - Eliezer, Wisly Ryan (Seminar Nasional Official Statistics, 2024)
The need for food is crucial for human life, no wonder it has become one of the common development goals by countries in the world related to ending hunger, obtaining food security, improving the quality of nutrition and proposing sustainable agricultural systems. Indonesia has problems in terms of food security, especially in Papua and West Papua with the lowest food security index value in 2022, even though these regions have extensive agricultural potential. This study aims to see an overview of the level of food security in Papua and West Papua and see the variables that affect it. The data used is data from 42 districts/cities in Papua and West Papua provinces sourced from the Central Bureau of Statistics and the Food Security Agency. The analysis method used is multiple linear regression. It was found that 25 districts/cities were still categorized as food insecure. Purchasing power and the level of public health are key factors to improve food security in Papua and West Papua.